Stravinsky and Maritain: Philosophies of work - Moody Ivan (Muzikologija, 2023)
Igor Stravinsky’s philosophical and religious trajectory included transformative encounters with Catholic theologians and philosophers in the Paris of the 1920s and 1930s. The most important amongst these was Jacques Maritain, whose neoThomist philosophy applied to art was of significance to Stravinsky, and in particular through its application in the life and work of fellow Russian émigré composer Arthur Lourié. This article examines the relationship between Stravinsky and Maritain in terms of the larger philosophical and creative context of the period, also touching on the work of Lourié and Manuel de Falla, and discussing its ramifications in the work of Stravinsky himself.